On the question of the system approach in small business - R. N. Botavina (Путеводитель предпринимателя)
The paper discusses the feasibility and effectiveness of using system theory in small business in times of crisis. The article states that the theory and practice of a systemic approach was previously used to increase the efficiency of large enterprises and organizations. The author proposes the application of the principles and methods of system theory for small businesses, and also emphasizes the need to increase the level of economic and financial literacy of entrepreneurs in small businesses, especially during crises.